Comparative Study on Mouth Dissolving Film and Mouth Dissolving Tablet for Naproxen - Tripathi, Alok Kumar; Vishwakarma, Dhaneshwar Kumar; Mishra, J.N (Journal of Neonatal Surgery, 2025)
The primary objective of this review is to explore the formulation and comprehensive evaluation of Mouth Dissolving Tablets (MDTs) and Mouth Dissolving Films (MDFs) containing Naproxen, utilizing two distinct formulation techniques: direct compression for tablets and solvent casting for films. These dosage forms were developed with the goal of enhancing the disintegration characteristics of Naproxen by employing various concentrations of functional excipients. Naproxen is a well-known non-steroidal anti-inflammatory drug (NSAID) and functions as a non-selective cyclooxygenase (COX) inhibitor. It is extensively prescribed for managing conditions such as rheumatoid arthritis, osteoarthritis, gout, and other musculoskeletal and inflammatory disorders. However, one of the major limitations of Naproxen is its poor aqueous solubility, coupled with a relatively long elimination half-life of approximately 12 to 17 hours, which can lead to delayed onset of therapeutic action. To overcome these formulation challenges and to achieve a rapid therapeutic response, both MDTs and MDFs were designed to facilitate faster drug release and absorption. In the tablet formulations, synthetic superdisintegrants such as croscarmellose sodium and sodium starch glycolate were incorporated to enhance the disintegration efficiency and promote quicker breakdown in the oral cavity. On the other hand, the film formulations employed polymeric film-forming agents including maltodextrin, polyvinyl alcohol (PVA), and hydroxypropyl methylcellulose (HPMC). These polymers not only aid in structural integrity and flexibility of the films but also significantly contribute to accelerated disintegration upon contact with saliva. The development of these novel oral dosage forms aims to provide better patient compliance, particularly in pediatric and geriatric populations, by eliminating the need for water during administration and offering a convenient and fast-acting alternative to conventional tablets or capsules